Relationships between postural stability in standing and handstand and psychological factors in athletes practicing artistic gymnastics - Omorczyk, J.; Zajac, A.; Puszczalowska-Lizis, E. (Baltic Journal of Health and Physical Activity, 2019)
The aim of this study was analyze relations between postural stability indices and selected psychological factors in athletes practicing artistic gymnastics. Material nad method: The study included 20 athletes practicing artistic gymnastics. The research tool was posturograph CQ-Stab 2P. The data were analyzed based on Pearson`s linear correlation, or alternatively Spearman`s rank correlation. Results: Statistically significant correlations of stability indicators registered in the handstand with the results of the Competitive State Anxiety Inventory - 2R CSAI questionnaire were found, in the absence of psychological variables with the results of stability tests in a free standing position with eyes open and without visual control. Conclusions: On this basis, we concluded that the psychological factor does not fundamentally affect the control of stability in standing which is natural position for human, even without inspection of the surroundings. The increase in the level of physical and cognitive anxiety and the decrease in self-confidence indicates a relationship with the deterioration of stability in the handstand position. In turn, the general conviction of the contestant to deal with difficult situations and obstacles, as well as the type of motivational orientation do not have a direct impact on stability.